A Multidisciplinary Approach to the Management of Hormone-Refractory Prostate Cancer - Taneja, Samir S (MedReviews, LLC, 2003)
The patient with hormone-refractory prostate cancer (HRPC) presents unique management challenges for both the urologist and the medical oncologist. Because of a lack of effective treatment options, the management of patients with HRPC has historically been palliative. Over the past 10 years, the advent of relatively efficacious chemotherapeutic regimens, particularly taxane-based chemotherapy, has resulted in a desire to treat patients with HRPC more aggressively. The complex needs of these patients have made a multidisciplinary approach, inclusive of specialists with expertise in disease processes directly affecting the patient, the optimal means of treating HRPC. An understanding of the natural history and complications of HRPC, combined with a systemic evaluative process, can allow the multidisciplinary team to comprehensively address the needs of the individual patient with HRPC.